Online Instructor Perceptions of Social Presence and Educational use of Social Media - Leafman, Joan S; Mathieson, Kathleen (Advances in Social Sciences Research Journal, 2015)
This study examined active online university instructors’ perceptions of social presence in a learning management system (LMS), use of social media tools, and willingness to use social media tools outside of an LMS to increase social presence. Data were collected via an anonymous electronic survey. Results indicated instructors perceived a high level of social presence in an LMS, but there were specific limitations. Subscription to multiple social media tools was common, but use of these tools for social communications with students or other instructors was rare. Instructors expressed a willingness to try social media tools outside an LMS to increase social presence. There is a continued and increasing demand for “virtual” education. While distance-provided curriculum, efficacy of online education delivery platforms and students’ characteristics, preferences, and learning styles are all studied, examination of the perceptions of faculty who facilitate learning in a distance format is limited. To achieve success in the cyberspace of education, understanding the behaviors and attitudes of instructors who lead the day-to-day operations of course facilitation are paramount to sustainability.